Imaging gait disorders in parkinsonism: a review. Issue 10 (8th July 2012) - Maillet, Audrey; Pollak, Pierre; Debû, Bettina
Abstract : Gait difficulties—including freezing of gait—are frequent and disabling symptoms of advanced Parkinson's disease and other parkinsonian syndromes. They respond poorly to current medical and surgical treatments, making patient management very difficult. The underlying pathophysiology remains largely unknown. The late onset of levodopa resistance of Parkinson's disease gait abnormalities has been suggested to result from the progressive extension of the degenerative process to non-dopaminergic structures involved in locomotion, such as cortico-frontal and brainstem networks. Deficiencies in other neurotransmission systems, involving acetylcholine, serotonin or norepinephrine, have also been evoked. Neuroimaging tools appear well suited to decipher the cerebral substrates of parkinsonian gait disorders and their modulation by dopaminergic medication or deep brain stimulation. Here the main functional and metabolic neuroimaging studies aimed at identifying these cerebral networks are reviewed, in both healthy subjects and parkinsonian patients. After a brief overview of the physiology and pathophysiology of gait control, the methodology, main results and limits of the studies published to date are examined. The most promising methods to examine gait difficulties and their response to currently available treatments are then discussed.